2014
DOI: 10.1039/c4mt00018h
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and preventive effects of platinum nanoparticles as reactive oxygen species scavengers on hepatic ischemia/reperfusion injury in mice

Abstract: Reactive oxygen species (ROS) are involved in the pathophysiology of ischemia/reperfusion injury. To protect mouse hepatocytes from ischemia/reperfusion injury, we prepared two different sizes of citric acid-protected platinum nanoparticles (Pt-NPs), which exhibited ROS-scavenging activities and selective delivery to a specific type of liver cell. Small Pt-NPs (30 nm) reduced the superoxide anion, hydrogen peroxide, and hydroxyl radical levels in solution to a greater extent than did large Pt-NPs (106 nm). Lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…10 In fact, PtNPs have also been found to attenuate oxidative injury in skin, brain, lung, and liver in the previous studies. [13][14][15][34][35][36] ROS scavenging is generally regarded as the primary cytoprotective and anti-inflammatory mechanism of PtNPs in mammalian cell lines such as Caco-2, HeLa, HT-1080, RAW264.7 and THP-1. [37][38][39][40][41] In line with Nomura et al (2011) and Rehman et al (2012), 41,42 PtNPs were observed to attenuate intracellular oxidant burst in RAW264.7 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…10 In fact, PtNPs have also been found to attenuate oxidative injury in skin, brain, lung, and liver in the previous studies. [13][14][15][34][35][36] ROS scavenging is generally regarded as the primary cytoprotective and anti-inflammatory mechanism of PtNPs in mammalian cell lines such as Caco-2, HeLa, HT-1080, RAW264.7 and THP-1. [37][38][39][40][41] In line with Nomura et al (2011) and Rehman et al (2012), 41,42 PtNPs were observed to attenuate intracellular oxidant burst in RAW264.7 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…PtNPs are known to possess ROS scavenging ability due to the catalytic activity contributed by its high ratio of electrons to particle surface [164]. PtNPs have demonstrated its therapeutic potential in several pre-clinical applications such as treating aging-related skin disease in SOD1 knockout mice [165], protection against UV-induced apoptosis in HaCaT keratinocytes [166], and prevention of hepatic injury from hepatic ischemia/reperfusion injury in mice [164].…”
Section: Strategies To Suppress Oxidative Stressmentioning
confidence: 99%
“…Notably, PtNPs are both biocompatible with and cytotoxic to various types of human cells [15][16][17][18]. For instance, PtNPs can act as scavengers of reactive oxygen species (ROS) [19,20], and they induce developmental alterations and increase heart rates in zebrafish [21]. Ultra-small PtNPs induce cellular stress, cytotoxicity, DNA damage, and genotoxicity in vivo and in vitro in human monocytic [22], U2OS [18], and prostate cancer (LNCaP) cell lines [17].…”
Section: Introductionmentioning
confidence: 99%